Pharmacokinetics and subjective effects of 1P‐LSD in humans after oral and intravenous administration. Issue 8 (2nd June 2020) - Grumann, Christina; Henkel, Kerstin; Brandt, Simon D.; Stratford, Alexander; Passie, Torsten; Auwärter, Volker
Abstract: 1‐Propanoyl‐lysergic acid diethylamide (1P‐LSD) appeared as a non‐controlled alternative to LSD a few years ago. Although evidence is beginning to emerge from in vitro and animal studies that 1P‐LSD might serve as a prodrug for LSD, an equivalent evaluation in humans is unavailable. Controlled oral and intravenous self‐administrations of 100 μg 1P‐LSD hemitartrate are reported in two human volunteers followed by analyses of urine and serum samples using a fully validated LC–MS/MS method. Psychometric evaluations included assessment of selected subjective drug effects and administration of the Five‐Dimensions of Altered States of Consciousness rating scale (5D‐ASC). In serum and urine, oral administrations of 1P‐LSD only led to the detection of LSD reflecting biphasic elimination with a terminal elimination half‐life of approx. t1/2 = 6.4 h. 1P‐LSD could be detected for only up to 4.16 h in serum and 2.7 h in urine following intravenous administration, whereas LSD was detected in all serum samples (last sampling after approx. 24 h) and up to 80 h in urine. LSD showed first order elimination kinetics with an approx. t1/2 = 5.7 h, whereas 1P‐LSD showed a rapid decrease in concentration within the first hour followed by a slower decrease, most probably due to hydrolysis. The bioavailability of LSD after oral ingestion of 1P‐LSD was close to 100%. The psychosensory effects of 1P‐LSD and their time course were comparable to those seen after uptake of LSD in other studies which further supports the prodrug hypothesis. The 5D‐ASC scores were higher after oral compared with intravenous administration of 1P‐LSD. Abstract : Controlled oral and intravenous administrations of 100 μg 1P‐LSD hemitartrate (equivalent to 71.2 μg LSD base assuming complete hydrolysis) in two human volunteers showed that it served as a prodrug of LSD. Psychometric evaluations suggested that the psychosensory effects of 1P‐LSD and their time course were comparable to LSD, the hydrolysis product of 1P‐LSD. 1P‐LSD was detected in serum and urine after i.v. administration only and for a very short time (approx. 4 h) before conversion to LSD was complete.